2000
DOI: 10.1139/z00-071
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the density of a sika deer population on activity, habitat use, and group size

Abstract: The influence of population density of sika deer (Cervus nippon) on their activity, habitat use, and habitatrelated group size was studied in the area of Japan's Tanzawa Mountains in early winter. The percentage of active sika deer was higher in January 1994 (a low-density period) than in January 1995 (a high-density period). The pattern of habitat use differed between periods. During the high-density period, deer increased their relative use of lower quality habitats. A possible mechanism and implications of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(22 citation statements)
references
References 39 publications
1
21
0
Order By: Relevance
“…Therefore the area occupied by this species (and presumably total population size) was smaller in more closed environments. Higher population densities, possibly related to larger group sizes (e.g., Khan et al, 1996;Borkowski, 2000) in open environments may have selected for reduced body size of E. ferus, because resources available for an individual were limited by intraspecific competition. We suggest that this combination of open-adaptedness and gregarious behaviour leading to large population densities in favourable conditions (open environments), is the most plausible explanation for the observed body size pattern of horses.…”
Section: Body Size and Synthesismentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore the area occupied by this species (and presumably total population size) was smaller in more closed environments. Higher population densities, possibly related to larger group sizes (e.g., Khan et al, 1996;Borkowski, 2000) in open environments may have selected for reduced body size of E. ferus, because resources available for an individual were limited by intraspecific competition. We suggest that this combination of open-adaptedness and gregarious behaviour leading to large population densities in favourable conditions (open environments), is the most plausible explanation for the observed body size pattern of horses.…”
Section: Body Size and Synthesismentioning
confidence: 99%
“…A similar case is the extant North American bison (Bison bison). According to Meagher (1986) the woodland subspecies (B. b. athabascae) is on average larger and moves in smaller groups than the plains subspecies (B. b. bison) which tends to form larger herds (probably increasing population density and intraspecific resource competition [see Khan et al, 1996;Borkowski, 2000]). Moreover, tests on the North American wapiti (Cervus elaphus canadensis) have shown that in a controlled situation where two populations, one with high density and one with low density, were compared yearly between 1998 and 2001, mean body mass was always reduced in the high-density population (Stewart et al, 2005).…”
Section: Body Size and Synthesismentioning
confidence: 99%
See 1 more Smart Citation
“…Because female white-tailed deer associate within matrilineal social groups while males tend to be alone or in small groups outside the breeding period (Nixon et al, 1991), these social groups may not change in size with deer density. However, changes in population density or size (Borowski, 2000;Hebblewhite and Pletscher, 2002) may affect the frequency and intensity of interactions among deer within or among social groups (Hirth, 1977;Nixon et al, 1991;Grenier et al, 1999;Kie and Bowyer, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…If Lyddeker ' s observations are representative, this would suggest a major shift in social structure over the past century. Group size in some ungulates is known to increase with population size (Borkowski 2000 ), so the smaller groups seen today might refl ect a population decline from a century ago. Alternatively, smaller group sizes today could refl ect declines in predation risk (Hamilton 1971 ) or resource distribution (Jarman 1974 ).…”
Section: Discussionmentioning
confidence: 99%